MON-160 The Burdens of Adrenal Insufficiency: A Survey Study from Two Tertiary Care Centers in the United States - Genere, Natalia (J Endocr Soc, 2020)
Background: Adrenal insufficiency (AI) is a chronic disorder necessitating life-long replacement. Patients’ quality of life and health outcomes depend on knowledge and comfort level with self-management. Objective: To determine patients’ knowledge in regards to diagnosis and management, estimate burden of disease and to identify predictors of adverse outcomes in patients with AI Methods: Survey study of patients with AI evaluated at two tertiary medical centers between 2015 and 2019. Collected variables included data on circumstances of AI diagnosis, symptoms, management, burden of disease, and overall well-being. Results: Among 785 patients (mean age at diagnosis 44.2 ± 18.0, 64% women, and 92% Caucasian), 310 (40%) had primary AI (PAI), 255 (33%) had secondary AI (SAI) not related to glucocorticoid use, and 211 (27%) had steroid-induced AI (SIAI). Patients were diagnosed with AI after presenting with symptoms for a median of 1 year (0-6), 28% with symptoms lasting >2 years, 44% visiting emergency room (ER) at least once prior to diagnosis. A third of patients reported a discordant diagnosis from their medical record. Baseline glucocorticoid replacement therapy included hydrocortisone (HC) in 447 (59%), median of 20 mg (IQR 15 - 25mg), prednisone in 190 (25%), median of 5 mg (IQR 4 - 7.5mg), other regimens in 38 (5%), and no steroids in the remainder (85, 11%); 197 (26%) patients reported daily equivalent HC dose of >25 mg. Overall, 549 (73%) of patients reported use of stress dose steroids at least once per year, higher in patients taking HC >25 mg/day (3.2 vs 2.7 times per year if HC<25mg/day, p=0.01). Improper use of stress steroids was reported in 193, 25% patients. Patients taking HC>25 mg /day reported a higher number of adrenal crises (1.6 vs 1.3 in patients on HC<25 mg/day, p=0.04). Among 314 (41%) patients who reported ER visits due to adrenal crisis, only a third received prompt glucocorticoids. One third of patients described their general health as fair or poor. Predictors of negative perceptions of overall health included SIAI (OR 6.2 and 2.5, vs PAI and SAI respectively), poor understanding of diagnosis (OR 2.6), daily HC>25 mg (OR 2.1), and presence of at least one adrenal crisis (OR 2.3) (p<0.001 for all). Conclusion: Patients with AI experience delay in diagnosis, and a third do not fully understand their diagnosis. In addition to patient education, interventions to improve general health and outcomes may include selecting a physiological glucocorticoid replacement therapy, prevention of adrenal crisis, and improving ER care.